The Role of Innovation and Intellectual Capital in Improving Company Performance - Maria Natasya Duka; Christiana Fara Dharmastuti (Universitas Trisakti, 2021)
Innovation and intellectual capital are essential factors that companies must pay attention to in maintaining their performance and business sustainability. Innovation decisions and investments intellectual capital require support from the owners to improve the company's performance. This study aims to analyze the innovation decisions studied through two strategies: demand-pull and technology push, and the role of intellectual capital in improving company performance, and moderated by family ownership. In this study, the demand-pull and technology push strategy is measured by looking at new product launches and purchases of new equipment by companies for a certain period. Intellectual capital is calculated by using the Value-Added Intellectual Coefficient (VAIC), then Return on Asset (ROA) to measure the company's performance. The subjects of this study were twenty-six (26) companies with family ownership engaged in consumer goods sectors and listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The data used were 130 including 30 data from the study were outliers. This study uses multiple linear regression moderation. The test results show that the innovation factors, namely demand-pull and technology push, and intellectual capital, positively influence company performance. However, family ownership weakens the influence of both innovation factors and can’t moderate the effect of intellectual capital on performance.